Periodontal Disease, Atherosclerosis, Adverse Pregnancy Outcomes, and Head-and-Neck Cancer. (May 2014) - Han, Y.W.; Houcken, W.; Loos, B.G.; Schenkein, H.A.; Tezal, M.
Interrelationships between periodontal infection and systemic conditions such as cardiovascular disease, adverse pregnancy outcomes, and head-and-neck cancer have become increasingly appreciated in recent years. Periodontitis is associated with cardiovascular disease (CVD) and, experimentally, with measures of atherosclerosis and endothelial dysfunction. Periodontal therapy may reduce atherosclerotic changes and improve endothe-lial function. Preliminary findings suggest a role for the genetic locus ANRIL in the pathobiology of both CVD and periodontitis. Periodontal pathogens induce anticardiolipin in periodontitis patients by molecular mimicry of the serum protein ß-2 glyco-proteinI. These antibodies have biological and pathological activities consistent with those reported for other infection-induced antiphospholipid antibodies. Anticardiolipin may explain some of the observed associations between periodontitis and systemic conditions such as CVD and adverse pregnancy outcomes. The oral commensal Fusobacterium nucleatum (Fn) becomes pathogenic on migration to extra-oral sites. Fn infection of the fetal-placental unit has been linked to pregnancy complications, including preterm birth, stillbirth, and earlyonset neonatal sepsis. Reagents aimed at inhibiting or resolving inflammatory responses may be used to treat or prevent pregnancy complications due to bacterial infection. Chronic periodontitis may be independently associated with head-and-neck squamous cell carcinoma (HNSCC) through direct toxic effects of bacteria and their products, and/or through indirect effects of inflammation. Additionally, chronic periodontitis may facilitate the acquisition and persistence of oral HPV infection, a recently emerged risk factor for HNSCC.